Acute urinary retention attributable to sacral herpes zoster. Issue 6 (20th October 2004) - Acheson, J; Mudd, D
Abstract : Acute urinary retention in women is uncommon. A 63 year old woman presented with suprapubic pain, a palpable bladder, and multiple grouped vesicles on the right buttock. Catheterisation showed a residual of 2000 ml. A case is reported of acute urinary retention secondary to herpes zoster infection of the sacral nerves (S2–4).